LEGAL ANALYSIS OF THE ROLE OF FINANCING INSTITUTIONS IN APPLYING LAW FIDUSIA GUARANTEE IN INDONESIA - Mutiari, Yunial Laili; Ramadhan, Muhammad Syahri; Irsan, Irsan (INTERNATIONAL JOURNAL OF RESEARCH IN LAW, ECONOMIC AND SOCIAL SCIENCES, 2019)
Use of collateral institutions is very popular and already familiar in the community and guarantee institutions have an important role in the framework of Indonesia's economic development Guarantee institutions that are currently developing rapidly is a Fiduciary Guarantee. The role of fiduciary guarantee institutions as one of the potential alternative funding sources to support the growth of the national economy should be well accommodated as stipulated in Law No. 42 of 1999 concerning Fiduciary Guarantee and OJK Regulation No. 29 / /POJK.05/2014 concerning the Implementation of the Business of the Financing Company. Most of the Financing Companies still have not registered the fiduciary guarantee deed due to a misunderstanding in elaborating the regulations regarding the collection of fiduciary guarantees stipulated in Law No. 42 of 1999 concerning Fiduciary Guarantee and OJK Regulation No. 29 / /POJK.05/2014 concerning the Implementation of Business of Financing Companies and Regulation of the Minister of Finance Number 130 / PMK 010/2012.